2023
DOI: 10.1021/acscatal.2c04388
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Rhodium Complexes: Precatalyst Activation-Triggered Bimetallic Enhancement for the Hydrosilylation Transformation

Abstract: To explore how to access bimetallic catalysts that can outperform their monometallic analogues, a set of mono- and bimetallic NHC/phosphine (NHC = N-heterocyclic carbene)-ligated rhodium(I) complexes were designed, synthesized, and characterized. The complexes were used as catalysts for the intermolecular hydrosilylation of diphenylacetylene. All four catalysts displayed significantly faster catalytic rates than the related complexes reported previously containing NHC/pyrazolyl donor ligands. The bimetallic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 82 publications
1
17
0
Order By: Relevance
“…[45][46][47][48] The improved efficiency of a bimetallic catalyst compared to its monometallic analog can be ascribed to cooperative interactions between the two metals and any possible electronic communication through bridging organic ligands. 49,50 Bimetallic catalysts can be of two types, viz. homobimetallic (same metals) and heterobimetallic (different metals).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[45][46][47][48] The improved efficiency of a bimetallic catalyst compared to its monometallic analog can be ascribed to cooperative interactions between the two metals and any possible electronic communication through bridging organic ligands. 49,50 Bimetallic catalysts can be of two types, viz. homobimetallic (same metals) and heterobimetallic (different metals).…”
Section: Introductionmentioning
confidence: 99%
“…substitution reactions. 55,56 For example, Pernik and coworkers 49 have shown that a bimetallic rhodium complex is more active than a monometallic catalyst for hydrosilylation. Similarly, a dinuclear nickel catalyst that is significantly more active than its mononuclear counterpart in alkyne hydrosilylation was reported by Uyeda and co-workers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,[13][14][15][16][17][18] Uyeda and coworkers have reported a bimetallic nickel complex containing a direct Ni-Ni bond promoting hydrosilylation of olefins with a broad substrate scope. 19 Similarly, a Rh(I) NHC/phosphine bimetallic complex, reported by Pernik and co-workers in 2023, effectively catalyses intermolecular hydrosilylation of alkyne with high selectivity, 20 displaying significant superiority over mono-rhodium catalysts with NHC-pyrazole donors. 20 Similarly, binuclear indium catalysts exhibited high catalytic activity for the ring-opening polymerization of lactide to form poly(lactic acid) at room temperature.…”
mentioning
confidence: 99%
“…19 Similarly, a Rh(I) NHC/phosphine bimetallic complex, reported by Pernik and co-workers in 2023, effectively catalyses intermolecular hydrosilylation of alkyne with high selectivity, 20 displaying significant superiority over mono-rhodium catalysts with NHC-pyrazole donors. 20 Similarly, binuclear indium catalysts exhibited high catalytic activity for the ring-opening polymerization of lactide to form poly(lactic acid) at room temperature. 21 Both bimetallic cobalt and ruthenium N-heterocyclic carbene complexes have been reported to promote the oxidation of water.…”
mentioning
confidence: 99%